Pengaruh Penambahan Ekstrak Khamir Terhadap Aktivitas Antibakteri Isolat Fungi Endofit Genus Paecilomyces Dari Kulit Buah Kakao (Theobroma Cacao L) - Asnurbaety Dwiyana (Jurnal Media Laboran, 2016)
A research about the effect of yeast extract addition on the antibacterial activity of endophytic fungi Paecilomyces genus from cacao pod husk (Theobroma cacao L.) has been conducted. The purpose of this research vas to know the effect of adding yeast extract on the antibacterial activity produced by endophytic fungi of cacao pod husk. Isolate of endophytic fungi fermented in Potato Dextrose Broth (PDB) medium with the addition of yeast extract 0.25% w/v, 0.5% w/v , 1 % w/v, 2% w/v, on a rotary shaker at 150 rpm for 7 days and then centrifuged at 3000 rpm for 15 minutes. The antibacterial activity of supematant was determined by measuring the growth inhibition of pathogenic bacteria Streptococcus mutans with agar diffusion method using paper disc for 24 hours incubation. The inhibition zone of negative control and sample with the addition of yeast extract 0.25% w/v, 0.5% w/v , 1% w/v 2% w/v to S mutans were 7.2 mm, 7.3 mm. 7.7 mm, 8.0 mm, and 8.4 mm respectively. These results indicated that yeast extract addition 1% w/v and 2% w/v have the most significantly influence toward antibacterial activity effect of endophytic fungi Paecilomyces genus.